MOTIVASI LATIHAN TIM BOLAVOLI PUTRA SMA OLAHRAGA MASMUR SELAMA MASA PANDEMI - M. Arif Rifaldi; Ramadi Ramadi; Syahriadi Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The goal to be achieved through this research is to find out the training motivation of the Masmur Sports High School men's volleyball team during the pandemic. This type of research is descriptive which aims to reveal how